PENGARUH LOYALITAS DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. SIMASJESS MULTIDAYA SOLUSI PALEMBANG - Fitantina; Randy Dwi Kurniawan; Efrina Masdaini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
This study aims to determine the effect of Loyalty and Job Satisfaction on Employee Performance at PT. Simasjess Multidaya Solusi Palembang simultaneously and partially. This type of research uses associative research, the variables used are Loyalty and Job Satisfaction and Employee Performance. The sample used was 53 respondents taken by Purposive Sampling method. The main data used is primary data using questionnaires and documentation. The results of the simultaneous hypothesis test show that there is a significant effect of Loyalty and Job Satisfaction on Employee Performance at PT. Simasjess Multidaya Solusi Palembang. The results of the partial hypothesis test show that there is a significant effect of Loyalty on Employee Performance at PT. Simasjess Multidaya Solusi Palembang. There is a significant effect of Job Satisfaction on Employee Performance at PT. Simasjess Multidaya Solusi Palembang. The results of the coefficient of determination show that the variables of Loyalty and Job Satisfaction are able to contribute to the rise and fall of Employee Performance by 65%.